2023
DOI: 10.3389/fmed.2022.1064449
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors associated with secondary open-angle glaucoma in Posner-Schlossman syndrome: A retrospective case-control study

Abstract: BackgroundPosner-Schlossman syndrome (PSS) is a relatively rare cause of chronic secondary open-angle glaucoma (OAG), but the exact cause is unknown. This study aimed to determine potential risk factors for OAG secondary to PSS and to provide a basis for early intervention in the development of PSS.MethodsThis was a retrospective case-control study. Nine cases diagnosed with PSS and seven cases diagnosed with OAG secondary to PSS were selected and their aqueous humor assays at the first occurrence of PSS were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Comparison of cytomegaloviruspositive and cytomegalovirus-negative PSS patients showed that the former had significant loss of corneal endothelial cells and the density was significantly lower than the latter, which may be associated with cytomegalovirus attacking the trabecular meshwork endothelial cells and corneal endothelial cells, resulting in increased IOP and corneal endothelial cell loss. The high possibility of rotavirus open angle glaucoma (OAG) in cytomegalovirus-positive PSS patients in the future should not be ignored, and regulation of IL-8 and IL-6 levels may be a new intervention to prevent OAG secondary to PSS [4] . Murata et al [5] treated 14 cases of PSS with trabeculectomy, and the surgical success (IOP <20 mm Hg) rate was up to 85.7%.…”
Section: Dear Editormentioning
confidence: 99%
“…Comparison of cytomegaloviruspositive and cytomegalovirus-negative PSS patients showed that the former had significant loss of corneal endothelial cells and the density was significantly lower than the latter, which may be associated with cytomegalovirus attacking the trabecular meshwork endothelial cells and corneal endothelial cells, resulting in increased IOP and corneal endothelial cell loss. The high possibility of rotavirus open angle glaucoma (OAG) in cytomegalovirus-positive PSS patients in the future should not be ignored, and regulation of IL-8 and IL-6 levels may be a new intervention to prevent OAG secondary to PSS [4] . Murata et al [5] treated 14 cases of PSS with trabeculectomy, and the surgical success (IOP <20 mm Hg) rate was up to 85.7%.…”
Section: Dear Editormentioning
confidence: 99%